Translation and Validation of the Edinburgh Postnatal Depression Scale for Eritrea: A Screening Tool for Postpartum Depression in Primary Health Care Facilities - Gebregziabher NK; Netsereab TB; Alazar FA; Fessaha YG; Sium AH; Ghebrehiwet NK (International Journal of Women's Health)
Nahom Kiros Gebregziabher,1,2 Tesfit Brhane Netsereab,1,3 Feven Andebrhan Alazar,4 Yerusalem Gebremeskel Fessaha,4 Aman Hadish Sium,4 Nardos Kidane Ghebrehiwet4 1Department of Community Medicine, Orotta College of Medicine and Health Sciences, Asmara, Eritrea; 2Department of Epidemiology & Biostatistics, School of Public Health, Tianjin Medical University, Tianjin, People’s Republic of China; 3Department of Epidemiology and Health Statistics, Xiangya School of Public Health, Central South University, Changsha, Hunan, People’s Republic of China; 4Ministry of Health, Asmara, EritreaCorrespondence: Nahom Kiros Gebregziabher, Department of Community Medicine, Orotta College of Medicine and Health Sciences, Asmara, Eritrea, Email nahomkiros21@gmail.comIntroduction: Postpartum depression (PPD) is a mood disorder characterized by symptoms such as changes in sleep and eating patterns, fatigue, sadness, crying, anxiety, and guilt. The Edinburgh Postnatal Depression Scale (EPDS) was developed to be used as a self-report questionnaire for English-speaking populations to screen for postnatal depression. This study aims to translate, validate, and adapt the EPDS into Eritrean settings.Methods: This study employed a cross-sectional study design to evaluate the performance of the EPDS as a screening tool by using a sample of 380 mothers from four primary healthcare facilities. The standard Diagnostic and Statistical Manual of Mental Disorders was used as a criterion to assess depression in postpartum women.Results: Postpartum depression was identified in 28 (7.4%) of the mothers based on the standard Diagnostic and Statistical Manual of Mental Disorders. The translated Tigrinya version EPDS has good internal consistency with Cronbach’s alpha of 0.712. The exploratory factor analysis identified three factors, confirming the EPDS’s multidimensionality. The area under the receiver operating characteristic curve was 0.87, and optimal sensitivity and specificity combination was found at 10/11 score cut-off points, 85.7% and 88%, respectively.Conclusion: The Eritrean version of EPDS has proven to be a valid and reliable instrument for the identification of postpartum depression in clinical settings.Plain language summary: Postpartum depression (PPD) is a significant concern affecting new mothers worldwide. Recognizing the need for practical screening tools tailored to specific cultural contexts, researchers set out to adapt and validate the Edinburgh Postnatal Depression Scale (EPDS).Why was the study done?Researchers aimed to adapt and validate the EPDS for Eritrea to provide a reliable tool for detecting PPD in mothers who recently gave birth. This is crucial as PPD is a severe condition affecting maternal and family well-being, and existing tools were not tailored for the Eritrean cultural context.What did the researchers do and find?The EPDS was translated into a local language and tested among new mothers in Asmara, Eritrea. Following the translation, they tested the scale’s reliability and validity by administering it to a group of new mothers in primary healthcare settings in Asmara, Eritrea. The findings were promising; the translated EPDS retained its reliability and validity, effectively identifying mothers experiencing symptoms of postpartum depression. This validation suggests the adapted EPDS is a robust tool for screening PPD in the Eritrean context.What do these results mean?The successful validation of the EPDS for Eritrean mothers is a significant advancement for maternal health care in Eritrea. Healthcare providers can now use this culturally and linguistically appropriate tool to screen for postpartum depression, leading to early detection and intervention. Improving screening can significantly enhance new mothers’ mental health and overall well-being, supporting healthier families and communities.Keywords: EPDS, postpartum depression, Eritrea, validation, mental health, Tigrinya